ESTIMATING CONTRIBUTION OFZOOXANTHELLAE TO ANIMAL RESPIRATION (CZAR) AND TO ANIMAL GROWTH (CZAG) OF GIANT CLAM Tridacna maxima - Ambariyanto A. (JOURNAL OF COASTAL DEVELOPMENT, 2006)
Zooxanthellae are symbiotic dinoflagellate algae which live in association with marine invertebratesincluding giant clams. These algae are capable of translocating part of their photosynthetic products tothe host. This translocation is one of the nutrition sources of the host. The present study aims tocalculate the contribution of zooxanthellae on the energy requirements of adult giant clam (Tridacnamaxima) during their respiration and growth processes. The result showed that zooxanthellae arecapable of contributing 260.67% and 452.54% energy required by giant clams for respiration andgrowth during summer and 171.51% and 273.51 % during winter, respectively. It suggests that all theenergy required for these two processes can be supplied by zooxanthellae.